PERANCANGAN E-REMINDER AKTIFITAS MAHASISWA PADA FAKULTAS TEKNIK UNIVERSITAS BHAYANGKARA JAKARTA RAYA - Dwi Swasono Rachmad; Gabriel Firsta Adnyana (Jurnal Teknologi Informasi dan Komputer, 2018)
ABSTRACT One of strategic that has been carried out by several universities in Indonesia to achieve quality academic and governance services is through the use of Information and Communication Technology (ICT) in the form of the use of academic information systems that contribute to improving the reputation of universities, as well as increasing user satisfaction. Lecture activities such as teaching and learning activities (KBM), the implementation of the semester exam, lecturer meeting is a daily operational activities. Teaching and learning activities are things that have become routine, but still often happens that students forget the academic activities that become obligations either because of a schedule change or other reasons. Regular schedule changes are usually distributed by the Administration to students or lecturers manually through a notice board The use of media boards raises difficulties for students, especially for students who have off-campus activities so the use of bulletin boards to convey information about lectures and academic activities among students became less effective. Therefore, an application is needed to help the delivery of information in realtime to remind students to carry out academic activities on schedule. Target to be achieved is to provide an e-reminder application of academic activities. This application consists of 3 users, the admin to enter the information mading, user (lecturer) to determine the schedule of guidance and user (student) to display the schedule of lectures, and the payment of the lecture along with notification of the schedule reminder so it can help and provide convenience for the administration in preparing and reminding activities to be carried out so that students can see about academic information and tuition payment information in real time both to students who are inside and outside the campus. Keywords : e-reminder, academic activities, mobile appABSTRAKBeberapa perguruan tinggi di Indonesia untuk mencapai pelayanan akademik dan tata kelola yang berkualitas adalah melalui pemanfaatan Teknologi Informasi dan Komunikasi (TIK) berupa penggunaan sistem informasi akademik yang berperan untuk meningkatkan reputasi perguruan tinggi, serta meningkatkan kepuasan pengguna Kegiatan belajar mengajar merupakan hal yang sudah menjadi rutinitas, namun masih seringkali terjadi mahasiswa yang lupa dengan aktifitas akademik yang menjadi kewajibannya karena adanya perubahan jadwal, ataupun hal lainnya. Perubahan jadwal regular biasanya didistribusikan oleh pihak Tata Usaha ke mahasiswa atau dosen secara manual melalui papan pengumuman. Penggunaan media papan pengumuman menimbulkan kesulitan bagi mahasiswa, terutama bagi mahasiswa yang mempunyai aktifitas di luar kampus sehingga penggunaan papan pengumuman untuk menyampaikan seputar informasi perkuliahan dan kegiatan akademik di kalangan mahasiswa menjadi kurang efektif. Aplikasi ini terdiri dari 3 pengguna, yaitu admin untuk memasukan informasi mading, user (dosen) untuk menentukan jadwal bimbingan dan user (mahasiswa) untuk menampilkan jadwal kuliah, dan pembayaran kuliah beserta notifikasi pengingat jadwal tersebut sehingga dapat membantu dan memberikan kemudahan bagi pihak tata usaha dalam menyusun serta mengingatkan kegiatan yang akan dilakukan sehingga mahasiswa dapat melihat seputar informasi akademik dan informasi pembayaran uang kuliah secara real time baik kepada mahasiswa yang berada didalam maupun diluar kampus.Kata kunci : e-reminder, aktifitas akademik, aplikasi mobile